Effects of exogenous bacterial quorum sensing signal molecule (messenger) N-hexanoyl- L-homoserine lactone (C₆-HSL) on morpho logical and physiological responses of winter wheat under simulated acid rain - Kosakivska, I.V.; Babenko, L.M.; Romanenko, К.О.; Futorna, O.A. (Доповіді НАН України, 2020)
This research aims to investigate the influence of foliar treatment by bacterial quorum sensing signal molecule/messenger N-hexanoyl-L-homoserine lactone (C₆-HSL, 100 ng/ml) on morphological and functional characteristics of Triticum aestivum L. cv. Yatran 60 leaves under simulated acid rain (SAR). Acid rain is one of the most dangerous abiotic stressor, which negatively affects the plant growth and development. It changes the permeability and photochemical activity of membranes, leads to the disruption of a chloroplast ultrastructure, stomata system functioning, reduces CO₂ photofixation. Using the scanning electron microscopy, we identified that, after the foliar treatment by C₆-HSL, the thickness of the leaf cell wall along with the cuticle layer in 20-day-old plants increased by 15 %. Under SAR condition, the plants have suffered the disruption of the cuticular wax layer and uneven wax plates on the epidermis surface, whereas the plants treated with C₆-HSL showed only a partial cracking of the cuticular wax layer, slight disruption of wax plates, and formation of a wax shell. The C₆-HSL-treated plants showed the normal functioning of stomata guard cells and the stabilization in the content of photosynthetic pigments. The protective effect of the foliar treatment with C₆-HSL solution in winter wheat plants under SAR and perspective of its using for the induction of stress resistance has been discussed.